Interplanetary Outpost The Human and Technological Challenges of Exploring the Outer Planets - Seedhouse, Erik (Space Exploration, 2012)
Water has been discovered on the Saturnian moon, Enceladus, and on Jupiter's moons, Europa, Ganymede, and Callisto. Where there is water, could there be life? Could this tantalizing possibility result in a manned mission to the outer planets? But how will such a mission be designed, what propulsion system will be used, and what hazards will the crewmembers face? Interplanetary Outpost describes step by step how the mission architecture will evolve, how crews will be selected and trained, and what the mission will entail from launch to landing. It addresses the effects that exteneded duration, radiation, communication, and isolation will have on the human body, and how not only performance but behavior might be affected.